Micro/Nanomotors: Phoretic Liquid Metal Micro/Nanomotors as Intelligent Filler for Targeted Microwelding (Adv. Mater. 51/2019). Issue 51 (17th December 2019) - Wang, Yong; Duan, Wendi; Zhou, Chao; Liu, Qing; Gu, Jiahui; Ye, Heng; Li, Mingyu; Wang, Wei; Ma, Xing
Abstract : In article number 1905067, Wei Wang, Xing Ma, and co‐workers report the fabrication of a liquid metal micro/nanomotor (LM‐MNM) made of Galinstan (a gallium–indium–tin alloy). These small LM‐MNMs (with a size of a few hundred nanometers) are half‐coated with a thin layer of platinum (Pt) and move in H2 O2 via self‐electrophoresis. Their potential as an on‐demand, self‐targeting welding filler is demonstrated through their movement and accumulation at junctions in a silver nanowire network.